Seasonal variations in testicular consistency, scrotal circumference and spermiogramme parameters of extensively reared Brahman (Bos indicus) bulls in the tropics - Pérez, E. (2002)
Twenty-five extensively bred mature Brahman (Bos indicus) breeding bulls were clinically examined and electroejaculated at monthly intervals for 13 months to study whether testicular consistency (TC), scrotal circumference (SC), sperm motility and sperm morphology show seasonal variation under tropical conditions. Changes in SC were positively related to body condition (BC) (beta = 0.7 cm, P < 0.001) and age (P < 0.01). However, these changes were not associated with deviations in TC, sperm motility, or morphology (P > 0.05). Sperm motility was higher in samples collected during the breeding season than in samples collected at other times (62 versus 52%, LSM, P < 0.01). The frequency of folded tails with trapped cytoplasmic droplets fluctuated among monthly ejaculations(LSM range 3-21%, P < 0.05). However, there was no relationship between these fluctuations and environmental temperature, precipitation or changes in BC, TC or SC of the bulls (P > 0.05). Other sperm abnormalities did not change significantly during the study period. The absence of a relationship between any of the climatic variables studied and SC, CT and sperm motility or morphology, respectively, indicates that temperature is not a major factor influencing reproductive performance in Brahman bulls in the tropics. In contrast, the changes found in bc followed by variations in SC suggest that nutrition may be an important factor affecting seasonal variations in male reproductive parameters, especially testicular size, in these sires.